Evolution and Dynamics of the Coherent Vortices in Contraction and Premix Coaxial Jets. Issue 4 (2nd February 2022) - Ba, Zhongren; Hao, Zhenhua; Li, Junguo; Yang, Xin; Li, Jiazhou; Zhao, Jiantao; Fang, Yitian
Abstract: Contraction and premix coaxial jets are commonly employed in gasification and combustion systems. Understanding the spatial development of coherent structures is a prerequisite to improve the mixing and stability characteristics. The evolution and dynamics of coherent vortices under the contraction and premix coaxial jets are visualized and discussed using flow visualization technology. The contraction configuration increases the instability of the outer shear layer corresponding to an organized rolling up of the outer vortex rings. In the premixed configuration, the earlier interaction between the inner and outer shear layers induces the precocious development of the inner Kelvin‐Helmholtz (K‐H) vortices. Two empirical equations are proposed to predict the transition length towards a fully turbulent flow. Abstract : The spatial evolution of the coherent vortices under the contraction and premix coaxial jets was experimentally investigated using flow visualization technology. The nozzle contraction and premix configurations can both promote the inner and outer shear layers' instability and accelerate the transition process from the axisymmetric vortex rings towards a fully developed turbulent flow.